ANALISIS KAJIAN SOCIAL MEDIA MARKETING DAN CUSTOMER ENGAGEMENT TERHADAP BRAND AWARENESS PLATFORM E-COMMERCE SHOPEE - Lamaindi, Yonatan; Zusrony, Edwin; Andriana, Myra; Manalu, Gibson (JURNAL LENTERA BISNIS, 2026)
The massive use of social media and the support of technology platforms have encouraged the younger generation to make product purchasing intentions on e-commerce. This study aims to determine the influence of Social Media Marketing (SMM) and Customer Engagement (CE) on Brand Awareness (BAW) for products through Shopee e-commerce among the younger generation in Yogyakarta, Indonesia. This study uses a quantitative approach involving 60 respondents aged 18-25 years and selected using a purposive sampling technique. The data analysis technique uses multiple linear regression and is processed using SmartPLS version 4.1.1.4 to test the influence and research hypothesis, to determine the relationship between variables. The research results show that the variables of Social Media Marketing and Customer Engagement have a positive and significant influence partially and simultaneously on Brand Awareness. These findings can be considered by e-commerce managers in communicating and delivering marketing offers online through social media.